Multilevel Analysis on the Predictors of Safe Sexual Behavior among Girl Adolescents in Karanganyar, Central Java - Melda Kumalaningrum; Eti Poncorini Pamungkasari; Ismi Dwi Astuti Nurhaeni (Journal of Health Promotion and Behavior, 2017)
Background: Studies have shown that the number of adolescents who have premarital sex is increasing. Unsafe sex can increase the risk of sexual transmitted disease, unwanted pregnancy, and suicide in adolescents. The study aimed to determine the associations between attitude, subjective norm, perceived behavior control, equal gender relation, and media exposure, on safe sexual behavior among girl adolescents in Karanganyar, Central Java.Subjects and Method: This was an analytic and observational study with cross-sectional design. The study was conducted in 25 senior high schools in Karanganyar, Central Java, from Desember, 2017 to January, 2018. A total sampel of 200 girl adolescents were selected by stratified random sampling, consisting of 8 girl adolescents from each of the 25 senior high schools. The dependent variable was safe sexual behavior. The independent variables were attitude, subjective norm, perceived behavior control, equal gender relation, and media exposure on safe sexual behavior. The data was collected using questionnaire and analyzed by multilevel analysis. The contextual effect of school, which distinguished rural and urban schools, on safe sex behavior was measured by intra-class correlation (ICC).Results: Positive attitude (b= 0.41; 95% CI= 0.14 to 0.69; p= 0.004), positive subjective norm (b=0.23; 95% Cl= 0.21 to 0.43; p= 0.031), strong perceived behavior control (b= 0.69; 95% Cl= 0.44 to 0.96 ; p< 0.001), equal gender relation (b= 0.41; 95% Cl =0.18 to 0.63; p<0.001), and exposure to media on safe sex behavior (b= 0.17; 95% Cl= -0.02 to 0.36; p= 0.085), predicted positively the likelihood of safe sexual behavior in girl adolescents. The contextual effect of school on safe sex behavior was small with ICC= 5.55%.Conclusion: Positive attitude, positive subjective norm, strong perceived behavior control, equal gender relation, and exposure to media on safe sex behavior, predict positively the likelihood of safe sexual behavior in girl adolescents.Keyword: predictor, safe sexual behavior, multilevel analysisCorrespondence: Melda Kumalaningrum. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36A, Surakarta. Email: melda.kumalanigrum@gmail.com. Mobile: 6282134359845.Journal of Health Promotion and Behavior (2017), 2(4): 323-331https://doi.org/10.26911/thejhpb.2017.02.04.04